Calculation of the Plastic Section Modulus Using the Computer - Bauer, Dominique Bernard (Engineering Journal, 1997)
A simple spreadsheet is presented which calculates the plastic section modulus of structural members. The method consists in dividing the cross section into rectangles and arranging all calculations conveniently into a spreadsheet program. The basic algorithm and the required spreadsheet formulas are given as well as a numerical example.